Dynamics of soil nutrients and biological activities along an infection chronosequence of pine wilt disease in subtropical Masson pine forests - Xueyu Song; Zunji Jian; Ke Wei; Xiaoyi Wang; Wenfa Xiao (Frontiers in Forests and Global Change)
Pine wilt disease (PWD) is a devastating forest disease that severely impacts pine trees, with widespread outbreaks leading to catastrophic damage in pine forests worldwide. Our study aims to investigate the dynamics of PWD infection on soil physicochemical properties and biological activities, as well as the interrelationships between them. Soil samples were collected from 0 to 10 cm and 10 to 20 cm depths in subtropical Pinus massoniana (Masson pine) forests with PWD infection years of 0 (non-infection), 6, 10, and 16 years. The physicochemical properties, microbial biomass, and enzymatic activities of these soil samples were measured. The results revealed that soil non-capillary porosity, clay, microbial biomass carbon and microbial biomass nitrogen decreased significantly in 6 years forests. Available potassium consistently decreased with longer invasion periods, while soil polyphenol oxidase, leucine amino peptidase, and available phosphorous peaked in 6 years forests and then declined over time. The soil physicochemical properties, biological activities all decreased as soil depth increased. Redundancy analysis and Mantel tests underscored the critical role of Total potassium, pH, Total phosphorous, and bulk density in shaping microbial activities. This study demonstrated that PWD infection significantly effect on soil physicochemical properties, microbial biomass, and enzymatic activities with the chronosequence progresses. These finding contribute to a deeper understanding of how invasive pathogens like PWD can reshape soil environments, with implications for forest conservation and restoration practices.